Construction and Validation of a Scale to Measure Antifeminist Attitudes - Roca, Marcelo Agustin (2025)
Background: One of the consequences of the widespread growth of feminism in the West has been the emergence of reactionary movements. These anti-feminist movements, with intense participation among young men, affirm that feminism seeks to violate male rights while reinforcing sexist and misogynistic ideals. Some people may oppose feminism due to misunderstandings about its goals, while others may hold more deeply rooted beliefs against gender equality. Despite the relevance of the topic, there are few works in general dedicated to tracing the attitudes that sustain antifeminism. Objective: The present study, conducted in Argentina, aims to build and validate an Antifeminist Attitudes Scale in Rioplatense Spanish. Method: The sample consisted of a total of 2171 subjects. A test was conducted to explore factors in one sample, followed by confirmatory analysis in another sample. Convergent validity was assessed by correlating with the Gender Role Identity scale, and gender disparities in antifeminist attitudes were examined. Results: The scale demonstrates an optimal degree of fit, good convergent validity, and a significant difference between men and women about the constructed scale. Results showed that men (vs. women) had higher scores in anti-feminism. Conclusion: The article presents the development and validation of a tool designed to assess antifeminist attitudes.